The Interplay between Cultural Heritage and Urban Morphology: A Case Study of uMlazi Cultural Landscape - Leonard Chitongo; Maheshvari Naidu (E-Journal of Humanities, Arts and Social Sciences)
Historic urban areas are a crucial component of urban heritage, arguably embodying the collective memory of urban development and often possessing distinctive urban textures and cultural attributes. This study analyses the relationship between intangible cultural heritage and urban morphology in uMlazi, a township in KwaZulu-Natal, South Africa. A dual theoretical framework informs the study. Through the dual lenses of the cultural landscape model and space syntax theory focused on a dynamic township environment, the study examined how intangible cultural heritage in open spaces and public amenities intersects with urban morphology to potentially shape community identity, social dynamics, and the built environment. The study explored how cultural heritage is crucial in defining uMlazi’s cultural landscape and influencing urban form and structure. It further examined the influence of key factors that impact the interplay between intangible cultural heritage and urban morphology, including historical context and urban planning policies. The study’s findings suggest that cultural heritage and indigenous knowledge systems play an integral role in urban planning and development initiatives to preserve community identity. The findings contribute to the growing research on cultural heritage and urban morphology, offering insights into township contexts’ unique challenges and opportunities.